Functional fixation: an investigation of the influence of earnings per share on company financing decisions - Mallin, Chris A. (1993)
In this thesis the various arguments that have been put forward for the determinants of a company's capital structure are examined critically. However, none of these succeeds convincingly in reflecting actual practice. Furthermore, it is argued that the common practice of concentrating on Earnings Per Share (EPS) as a key indicator of a company's performance also impacts on the capital issue choice, and that there is functional fixation on EPS, particularly short-term EPS. Therefore the effect on a company's EPS of a particular method of finance turns out to be an important influence on a company's financing decisions. A questionnaire sent to finance directors of companies elicits their views on their perceptions of the important influences on the choice of financing, and the responses are analysed using multivariate techniques. The results are encouraging as far as the present research question is concerned. An innovative approach of reconstructing company's financial statements to investigate the impact on various financial data if an alternative financing method had been chosen provides further evidence of a fixation on EPS. Limited dependent variable analysis is carried out to determine the variables which appear to influence the debtequity choice. A by-product of the research question is an analysis of 'elasticity' measures of gearing, i. e. degrees of financial and operating leverage; and the usefulness and consistency of the bases of measurement used for these. This thesis seeks to determine the extent to which financial choice is explained by, or at least consistent with, the maximisation of Earnings Per Share. In so doing, it seeks to provide a vital link between finance research and related financial accounting issues.